Impact of asthma and allergic rhinitis control on sleep disordered breathing in pediatrics - Catarina Isabel Medalhas Rebelo da Silva; Rosa Martins; Rosário Ferreira (Sleep Medicine: X)
Aim: The aim of our study is to assess the quality of sleep in children with asthma and/or allergic rhinitis, as well as the impact of the control of allergic respiratory diseases on sleep disturbances. Materials and methods: It is an observational cross-sectional study on children attending pediatric allergy appointments at a portuguese tertiary hospital (G1), and compared to a control population (G2). The asthma and rhinitis control was determined using the Control of Allergic Rhinitis and Asthma Test (CARAT/CARATKids) questionnaires. Sleep was evaluated using the Pediatric Sleep Questionnaire (PSQ). G1 included 61 patients and G2 included 100 children. Results: About a third of the children in the study group had sleep-related breathing disorders (SDB), compared to 9 % on the control group (p-value <0.05). There was a significant positive correlation between uncontrolled asthma and allergic rhinitis, and SDB (p-value <0.05). Conclusion: SDB is more prevalent among children with asthma and/or allergic rhinitis. The absence of control of the allergic respiratory diseases has a negative impact on sleep. We recommend large cross-sectional studies to better comprehend the exact relationship between the two conditions, as well as the use of objective diagnostic tools. We believe it is essential to implement early screening for sleep disorders in children with allergic respiratory diseases, through validated questionnaires.